Bentuk Penyajian Silek Kapak Sebagai Budaya Tradisi Masyarakat Di Kanagarian Padang Laweh Kecamatan Koto Tujuah Kabupaten Sijunjung - Chelina Dewi; Indrayuda Indrayuda (SENDRATASIK UNP, 2021)
The research aims to reveal, describe and analyze about the Form of Presentation of Silek Axe as a Culture of Community Tradition in Kanagarian Padang Laweh District Koto Tujuah Sijunjung Regency. This type of research is qualitative research with descriptive methods of analysis. The data type uses primary data and secondary data. The main instruments are the researchers themselves and are assisted with supporting instruments such as stationery and cameras. Data collection techniques are conducted by way of literature, observation, interview and documentation. The steps to analyze data are data collection, data reduction, data presentation, and conclusion drawing. The results of this study show that Silek Kapak is a tradition of Padang Laweh people. Silek Axe was performed by 2 players, which was displayed in the courtyard of Rumah Gadang during the day. The form of presentation of Silek Axe in Kanagarian Padang Laweh Sub-District Koto Tujuah Sijunjung Regency is representative. Elements of Silek Axe Presentation Form as follows: (1) opening greeting motion, amuak kapalo, amuak dado, pata tobu, klotiak and closing greetings. (2) Silek Axe floor pattern uses a straight line pattern or horizontal line. (3) Silek Axe's accompanying music consists of: talempong, drums, gongs. (4) the costume used by the player in Silek Axe taluak balango in black, black pants, asamping and deta. (5) In addition, Silek Axe uses the Original Axe property as supporting silek axe show.